2014
DOI: 10.1155/2014/242048
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of HLA Class I and II Alleles and Haplotypes with Autism: A Case Control Study

Abstract: Earlier reports showed the relationship between autism and immune genes located in the human leukocyte antigen (HLA). In this current study, we compared the HLA class I and class II alleles and haplotypes in 35 autistic children with 100 control subjects from Saudi Arabia, using PCR-SSP method and Luminex technology. In class I the HLA-A*01 (P = 0.03, OR 2.68), A*02 (P = 0.001, OR 3.02) and HLA-B*07 (P = 0.01, OR 3.27), were significantly associated with autism. Also, the haplotype A*02-B*07 was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…Multiple studies have suggested HLA-DR4 as another risk factor, appearing at increased rates in children with autism as well as their mothers (Johnson et al, 2009;Lee et al, 2006). Other positively associated alleles are the class I A*01, A*02, and B*07, while DRB1*03 and some DQB1 alleles have been negatively associated with rates of autism (Al-Hakbany et al, 2014;Mostafa et al, 2013;Torres et al, 2006). Interestingly, Guerini et al (2015) discovered a 14-basepair insertion in HLA-G that was found more often in individuals with ASD and their mothers.…”
Section: Immunogenetic Factorsmentioning
confidence: 99%
“…Multiple studies have suggested HLA-DR4 as another risk factor, appearing at increased rates in children with autism as well as their mothers (Johnson et al, 2009;Lee et al, 2006). Other positively associated alleles are the class I A*01, A*02, and B*07, while DRB1*03 and some DQB1 alleles have been negatively associated with rates of autism (Al-Hakbany et al, 2014;Mostafa et al, 2013;Torres et al, 2006). Interestingly, Guerini et al (2015) discovered a 14-basepair insertion in HLA-G that was found more often in individuals with ASD and their mothers.…”
Section: Immunogenetic Factorsmentioning
confidence: 99%
“…alleles were selected in another study, but none of these alleles showed consistent results (16). Al-Hakbany et al (28) could only find HLA-B * 07 significantly associated with ASD in his case-control study, the extended haplotype HLA-A * 02-B * 07 was significantly higher in ASD compared to controls. The reason that causes these conflicting results could be complex.…”
Section: Discussionmentioning
confidence: 91%
“…Similar to AD, other studies have also implicated the HLA-DRB5 region in PD risk [72]. In one small autism study, the class I allele B*07 and class II allele DQB1*06 : 02 were both associated with disease risk [73]. Finally, class II allele DQB1*06 : 02 has been associated with marked increased risk for [74,75], and worsened severity of [76,77], narcolepsy.…”
Section: Discussionmentioning
confidence: 92%